Cognitive and linguistic predictors of word reading fluency in Turkish-Arabic bilingual and Turkish monolingual children - Ilerten, Ferda; Haznedar, Belma; Babur, Nalan (SAGE PUBLICATIONS LTD, 2026)
Objectives: The study investigated the role of linguistic and cognitive factors in Turkish word reading fluency (WREAD) among second-grade Turkish-Arabic simultaneous bilingual and Turkish monolingual children. It specifically focused on the impact of phonological awareness (PA), phonological memory (PM), rapid automatized naming (RAN), morphological awareness (MA), morphological fluency (MF), processing speed (PS), and vocabulary knowledge (VK) on reading fluency.Methodology: The study used a cross-sectional design and collected data from 127 children in Hatay, Turkey. The participants completed a battery of tests measuring PA, PM, RAN, MA, PS, VK, and WREAD. The tests were administered individually, and the scores, along with the time spent on each test, were recorded.Data and analysis: Data from the tests were analyzed using SPSS 22.0. Independent samples t-tests were conducted to determine the differences between bilingual and monolingual children in the linguistic and cognitive measures. Pearson r correlation analyses were conducted to illustrate the relationship among the variables and stepwise regression analyses to explore the extent to which these variables explained the variance in WREAD.Findings: The findings highlighted significant differences between Turkish-Arabic bilingual and Turkish monolingual children in PA and PS. While MF and RAN explained WREAD in the bilingual group, MF and PA were the strongest predictors of WREAD in the monolingual children.Originality: This study is the first to investigate word reading development in Turkish-Arabic simultaneous bilingual children, contributing novel insights into literacy acquisition in simultaneous bilingualism. In addition, the concept of MF has been proposed in the literature as a distinct measurement from MA.Significance: The study expands the existing knowledge on bilingual reading development, emphasizing the importance of timed cognitive and linguistic variables in predicting WREAD. It also sheds light on the educational needs of bilingual children in the Turkish context.
Keywords: Bilingualism; reading development; morphological fluency; simultaneous bilingualism; PHONOLOGICAL PROCESSING ABILITIES; MORPHOLOGICAL AWARENESS; NAMING SPEED; COMPREHENSION SKILLS; LITERACY SKILLS; LANGUAGE; VOCABULARY; ENGLISH; MEMORY; CONSEQUENCES; Linguistics